A validated HPLC‐MS/MS method for determination of genipin‐1‐o‐glucuronic acid in rat plasma after administration of genipin and its application to a pharmacokinetic study. (4th September 2013) - Ding, Yue; Zhang, Yong; Zhang, Tong; Peng, Ming; Tao, Jian‐Sheng; Ji, Guang
ABSTRACT: A sensitive and specific method was developed and validated for the quantitation of one major metabolite of genipin in rats plasma. The major metabolite was isolated from rat bile via semi‐preparative HPLC technology and its chemical structure was identified as genipin‐1‐ o ‐glucuronic acid (GNP‐GLU), which was for the first time used as a standard compound for quantitative analysis in rat plasma after administration of genipin. The application of high‐performance liquid chromatography–tandem mass spectrometry in negative mode in multiple reaction monitoring mode was investigated. Chromatographic separation was achieved on an Eclipse XDB‐C18 column using a mobile phase consisting of water with 0.1% formic acid (A)–acetonitrile (B). The limit of detecation was 0.214 ng/mL and the lower limit of quantification was 0.706 ng/mL. The calibration curve was linear from 1.27 to 3810 ng/mL for plasma samples, with a correlation coefficient of 0.9924. The intra‐ and inter‐day precisions and accuracy were all within 15%. The recoveries of GNP‐GLU and puerarin were above 90.0 and 76.2%, respectively. The highly sensitive method was successfully applied to estimate pharmacokinetic parameters of GNP‐GLU following oral and intravenous administration of genipin to rats. Copyright © 2013 John Wiley & Sons, Ltd.